2004
DOI: 10.1002/bdra.20042
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologic characteristics of anotia and microtia in California, 1989–1997

Abstract: These data reveal descriptive epidemiologic features of anotia/microtia most notably substantial risks associated with race/ethnic groups and lower maternal education. Additional study for factors associated with these characteristics could reveal clues for the etiology of these ear anomalies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

22
142
4
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 118 publications
(169 citation statements)
references
References 12 publications
22
142
4
1
Order By: Relevance
“…The obvious predominance of unilateral cases and among them a slight right side excess in cases with isolated microtia/anotia in our study corresponded to the previous observations in other studies/countries [11,13,15,[18][19][20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The obvious predominance of unilateral cases and among them a slight right side excess in cases with isolated microtia/anotia in our study corresponded to the previous observations in other studies/countries [11,13,15,[18][19][20][21][22][23][24][25].…”
Section: Discussionsupporting
confidence: 92%
“…The mild male excess of cases with isolated ear CAs in the study was in agreement with the results of some previous studies [11,13,15,[18][19][20][21][22][23], though the cases with isolated microtia/anotia in the Italian registry did not show a male predominance [24]. The strong male excess in cases with unclassified multiple ear CA is worth mentioning, because in general previous studies did not have strict differentiation between cases with isolated and multiple ear CAs.…”
Section: Discussionsupporting
confidence: 91%
“…Maternal obesity is also a risk factor for NTDs and other birth defects, possibly due to a similar mechanism [Waller et al, 2007;Stothard et al, 2009]. Some descriptive characteristics of increased NTD risk, such as low maternal education and Hispanic ethnicity, are also seen among infants with microtia [Shaw et al, 2004;Canfield et al, 2009]. Given these epidemiologic similarities between microtia and NTDs, we explored the potential association of microtia with maternal obesity and periconceptional intake of folic-acid-containing supplements.…”
Section: Introductionmentioning
confidence: 96%
“…There is a paucity of epidemiologic information about this condition, and most previous studies have been descriptive. These studies have revealed that risk factors for microtia include advanced maternal age [Harris et al, 1996;Forrester and Merz, 2005;Canfield et al, 2009], male sex [Harris et al, 1996;Shaw et al, 2004;Canfield et al, 2009], low maternal education [Shaw et al, 2004;Husain et al, 2008;Canfield et al, 2009], and Hispanic ethnicity [Harris et al, 1996;Shaw et al, 2004;Forrester and Merz, 2005;Husain et al, 2008;Canfield et al, 2009]. Proposed etiologies include hypoxia [Castilla et al, 1999], in utero exposure to thalidomide [Buyse, 1990;Carey, 1993], maternal influenza [Lopez-Camelo and Orioli, 1996], and maternal diabetes [Mastroiacovo et al, 1995;EwartToland et al, 2000;Correa et al, 2008].…”
Section: Introductionmentioning
confidence: 96%
“…Microtia has an incidence of 1 in 7000 to 8000 births in the general population [2,3] . Males are affected more commonly, and the reported ratio of right-to-left-to-bilateral is approximately 5:3:1 with bilateral deformity occurring in only 10% of patients [4,5,6,7].…”
Section: Introductionmentioning
confidence: 99%